Influence of the ferrule effect on the failure of fiber-reinforced composite post-and-core restorations: A systematic review and meta-analysis - Batista, Victor Eduardo de Souza; Bitencourt, Sandro Basso [UNESP]; Bastos, Natália Almeida; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP] (Elsevier, 2019)
Statement of problem: The survival and/or success of post-retained restorations is influenced by the amount of residual coronal structure, known as the “ferrule effect.” Purpose: The purpose of this systematic review and meta-analysis was to evaluate whether the presence or absence of the ferrule effect influences the failure rate of fiber-reinforced composite post-and-core restorations. Material and methods: A comprehensive review of the literature was performed using the PubMed/Medline, Embase, Scopus, and Cochrane Library databases for articles published up to May 2018. The risk ratio with 95% confidence interval was estimated using the Mantel-Haenszel method. Potentially eligible studies were selected based on the reading of the abstracts and full text of prospective clinical trials, randomized clinical trials, or prospective randomized studies, all with a minimum of 10 participants in each group, with a follow-up period longer than 6 months, and published in English. Results: Of the 380 studies retrieved, 4 were included in this meta-analysis. A total of 297 teeth were evaluated, 157 with a ferrule and 140 without a ferrule. The mean survival rate was 88.35% in the ferrule group and 78.05% in the nonferrule group. No statistically significant difference was noted in the general failure analysis (risk ratio: 0.71 [95% confidence interval: 0.47 to 1.06]; P=.09), although a higher number of failures occurred in nonferrule restorations. More controlled and randomized clinical trials are needed to establish a clinical protocol for the use of post-retained restorations. Conclusions: Despite the limited number of available studies, the results of this meta-analysis suggest that the ferrule effect does not significantly reduce the failure rate in fiber-reinforced composite post-and-core restorations.